Association between operator volume and mortality in primary percutaneous coronary intervention. Issue 2 (3rd October 2022) - Krishnamurthy, Arvindra; Keeble, Claire M; Anderson, Michelle; Burton-Wood, Natalie; Somers, Kathryn; Harland, Charlotte; Baxter, Paul D; McLenachan, Jim M; Blaxill, Jonathan M; Blackman, Daniel J; Malkin, Christopher J; Wheatcroft, Stephen B; et al.
Abstract : Background: There is a paucity of real-world data assessing the association of operator volumes and mortality specific to primary percutaneous coronary intervention (PPCI). Methods: Demographic, clinical and outcome data for all patients undergoing PPCI in Leeds General Infirmary, UK, between 1 January 2009 and 31 December 2011, and 1 January 2013 and 31 December 2013, were obtained prospectively. Operator volumes were analysed according to annual operator PPCI volume (low volume: 1–54 PPCI per year; intermediate volume: 55–109 PPCI per year; high volume: ≥110 PPCI per year). Cox proportional hazards regression analyses were undertaken to investigate 30-day and 12-month all-cause mortality, adjusting for confounding factors. Results: During this period, 4056 patients underwent PPCI, 3703 (91.3%) of whom were followed up for a minimum of 12 months. PPCI by low-volume operators was associated with significantly higher adjusted 30-day mortality (HR 1.48 (95% CI 1.05 to 2.08); p=0.02) compared with PPCI performed by high-volume operators, with no significant difference in adjusted 12-month mortality (HR 1.26 (95% CI 0.96 to 1.65); p=0.09). Comparisons between low-volume and intermediate-volume operators, and between intermediate and high-volume operators, showed no significant differences in 30-day and 12-month mortality. Conclusions: Low operator volume is independently associated with higher probability of 30-day mortality compared with high operator volume, suggesting a volume–outcome relationship in PPCI at a threshold higher than current recommendations.